2009
DOI: 10.1128/aac.01374-08
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Lopinavir Predict Suboptimal Therapeutic Concentrations in Treatment-Experienced Human Immunodeficiency Virus-Infected Children

Abstract: In adult protease inhibitor (PI)-experienced patients, a lopinavir (LPV) phenotypic inhibitory quotient (PIQ) of >15 has been associated with a higher likelihood of viral suppression. The aims of this study were to develop a population pharmacokinetic (PK) model of LPV in children and to estimate the probability of achieving a PIQ of >15. HIV-infected, PI-experienced children receiving LPV were intensively sampled for 12 h to measure plasma LPV. The data were fitted to candidate PK models (using MM-USCPACK sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Finally, as we reported in our population PK analysis for LPV [38] , in this study we also found a significant association between RTV CL and age, due to age related changes in apparent volume of distribution that were independent of weight. For both drugs, the weight-adjusted volume of distribution in L/kg on average diminishes with age, which is likely a reflection of the age-related reduction in extracellular body water as a percentage of total body weight.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, as we reported in our population PK analysis for LPV [38] , in this study we also found a significant association between RTV CL and age, due to age related changes in apparent volume of distribution that were independent of weight. For both drugs, the weight-adjusted volume of distribution in L/kg on average diminishes with age, which is likely a reflection of the age-related reduction in extracellular body water as a percentage of total body weight.…”
Section: Discussionsupporting
confidence: 86%
“…Body weight was introduced as allometric scaling for oral clearance and volume of distribution of both LPV and ritonavir which is in agreement with previous studies in children [16,17]. Jullien et al [16] observed a 39% increase in oral clearance of LPV after the age of 12 years for boys.…”
Section: Discussionsupporting
confidence: 76%
“…This finding is consistent with higher variability of lopinavir/ritonavir in children and is possibly due to age, physical and sexual maturation and weight differences of the subjects. (2527) In our study, the decrease in AUC ranged from 5% to as high as 75%. Similarly, decreases in C max and C 12 varied greatly, albeit to a lesser extent than AUC.…”
Section: Discussionmentioning
confidence: 45%